Synthesis, Characterization, and Antimicrobial Studies of N, O Donor Schiff Base Polymeric Complexes - Shubhangi N. Kotkar; Harjeet D. Juneja (Journal of Chemistry)
A series of new polymeric complexes of Mn(II), Co(II), Ni(II), Cu(II), and Zn(II) were prepared with a Schiff base ligand derived from condensation of 2,4-dihydroxy acetophenone and p-phenylene diamine and characterized by elemental analysis and IR and NMR spectral data. The antimicrobial activity of the Schiff base and its polymeric complexes have been studied.